The Influence Of Electronic Word Of Mouth (E-Wom) On Impulse Buying Behaviour For Nuface Products On The Tiktok Platform (Case Study Of Feb-Unived Students) - Mukmin, Suprian Fikril; Irwanto, Tito; Abi, Yudi Irawan (Journal of Management, Economic, and Accounting, 2025)
The rapid development of information and communication technology, along with the emergence of advanced smartphones, has driven the increasing use of social media, including TikTok. TikTok, through its TikTok For Business feature, has become a potential platform for promotional strategies, including for Nuface, which employs an Electronic Word of Mouth (E-WOM) strategy. However, the trend of product de-influencing, which encourages consumers to avoid impulsive purchases, has left Nuface trailing behind its competitors. In Indonesia, impulsive buying behavior is relatively common, with 35% of consumers attracted by appealing promotions, and 56.7% of students struggling to control their impulsive purchases. This study aims to analyze the relationship between E-WOM and impulsive buying behavior for Nuface products. The research is associative, involving 100 respondents selected through non-probability sampling methods, specifically purposive sampling and accidental sampling. Data were analyzed using descriptive analysis techniques, Spearman's rank correlation coefficient, and hypothesis testing. The results indicate that Nuface's E-WOM strategy achieved an average score of 84.1%, signifying that Nuface's E-WOM is quite effective among students. Impulsive buying of Nuface products also recorded an average score of 82.5%, indicating that students tend to engage in impulsive buying. Although the correlation between E-WOM and impulsive buying is relatively weak, hypothesis testing showed significant results with a p-value < α (0.006 < 0.05), indicating a significant relationship between E-WOM and impulsive buying of Nuface products.